Integration of Semi-Automated Routing Algorithms for Spatial Circuit Carriers into Computer-Aided Design Tools - Zeitler, Jochen; Fischer, Christian; Goetze, Bernhard; Franke, Jörg (Electronics Circuit World Convention 13 (ECWC 13), 2014)
Though the market for 3D Molded Interconnect Device applications increases fast, the engineering process of these mechatronic assemblies still lag behind. The integration of electronic and mechanical design on mechatronic assemblies with complex spatial surfaces is a challenging task in the development process. This paper describes a method to create a MID specific product model that fulfills both requirements. This is on the one side the electrical design and on the other side the mechanical design. Both are considering design- and manufacturing rules, respectively keep-out areas. This product model is tied to two different mechanical computer-aided design systems, AutoCAD Inventor on the one side and Siemens NX on the other side. Furthermore the concept to flatten the 3D-circuitry, suitable for the surfaces of volume bodies, to ease 3D routing, will be discussed in this paper.
Keywords: MID; Design; CAD